While studying polylogarithms I observed the following.

Let $n>0$ and $k>1$ be integers. Is the following statement true?

$$\left\lfloor \sum_{s=1}^n \operatorname{Li}_s\left( \frac{1}{k} \right) \right\rfloor \stackrel{?}{=} \left\lfloor \frac{n}{k} \right\rfloor $$

If it is, then how could we prove it? If not, give a counterexample.


We use the series expansion for the polylogarithm.

Note that

$$\sum_{s=1}^{n}\operatorname{Li_{s}}\left(\frac{1}{k}\right) = \sum_{s=1}^{n}\sum_{j=1}^{\infty}\frac{1}{j^sk^j} = \sum_{j=1}^{\infty}\sum_{s=1}^{n}\frac{1}{j^{s}k^j}$$

we are able to interchange the summations because each term is positive, which implies that the sum is absolutely convergent.

Now separating out the first term gives

$$\frac{n}{k} + \sum_{j=2}^{\infty}\sum_{s=1}^{n}\frac{1}{j^sk^j}$$

We may then use the formula for a geometric sum to bring this to

$$\frac{n}{k} + \sum_{j=2}^{\infty}\frac{1}{j}\frac{1 - \frac{1}{j^{n+1}}}{\left(1 - \frac{1}{j}\right)k^j} = \frac{n}{k} + \sum_{j=2}^{\infty}\frac{j^{n+1} - 1}{j^{n+1}\left(j-1\right)k^j} = $$

$$\frac{n}{k} + \sum_{j=2}^{\infty}\frac{1}{\left(j-1\right)k^j} - \sum_{j=2}^{\infty}\frac{1}{j^{n+1}\left(j-1\right)k^j}$$

Now since clearly

$$\sum_{j=2}^{\infty}\frac{1}{\left(j-1\right)k^{j}} > \sum_{j=2}^{\infty}\frac{1}{j^{n+1}\left(j-1\right)k^j}$$

we have

$$\frac{n}{k} < \sum_{s=1}^{n}\operatorname{Li}_{s}\left(\frac{1}{k}\right) < \frac{n}{k} + \sum_{j=2}^{\infty}\frac{1}{\left(j-1\right)k^j} = \frac{n}{k} + \frac{1}{k}\sum_{j=1}^{\infty}\frac{1}{jk^j} = \frac{n}{k} + \frac{\log\left(\frac{k}{k-1}\right)}{k}$$

where we have used one of the series for $\log$ given here. The series is valid since $k \geq 2$.


$$\frac{n}{k} < \sum_{s=1}^{n}\operatorname{Li}_{s}\left(\frac{1}{k}\right) < \frac{n}{k} + \frac{\log(k) - \log(k-1)}{k}$$

Now for $n$ and $k$ natural numbers, the smallest possible difference between $\left \lfloor \frac{n}{k}\right \rfloor + 1$ and $\frac{n}{k}$ is $\frac{1}{k}$.

Thus the result will hold if $$\frac{\log(k) - \log(k-1)}{k} < \frac{1}{k}$$

or in other words if

$$\log(k) - \log(k-1) < 1$$

It's easy to check that $\log(x) - \log(x-1)$ is monotonically decreasing for $x > 1$. Also $\log(2) - \log(1) = \log(2) < 1$. It follows that the result holds for all natural numbers $k \geq 2$.

| cite | improve this answer | |

Some observaions:

For the case $k=1$ we have $$\sum_{s=1}^n\operatorname{Li}_s(1)=\sum_{s=1}^n\zeta(s)$$ Which is undefined unless you take $\zeta(1)=-1/12$.

However through checking through Mathematica it is apparent that ignoring or extending $\zeta(1)$ gives the same answer which happens to be $$\left\lfloor\sum_{s=1}^n\operatorname{Li}_s(1)\right\rfloor\stackrel{?}{=}n-1$$

  • $\begingroup$ @user153012 As I said it doesn't matter. $\endgroup$ – Ali Caglayan Sep 29 '14 at 16:44

For this proof to work, we have to add the restriction that $k \geq 2$, since $\operatorname{Li}_1\left( \frac{1}{1} \right)$ doesn't even converge anyway.

Now, by the definition of the polylogarithm, we have: \begin{align} \sum_{s=1}^n \operatorname{Li}_s\left( \frac{1}{k} \right) &=\sum_{s=1}^n \sum_{j=1}^\infty {1 \over j^s k^j} \\&=\sum_{j=1}^\infty \frac{1}{k^j} \sum_{s=1}^n \frac{1}{j^s} \\&=\frac{n}{k}+\sum_{j=2}^\infty \frac{1}{k^j} \left( {1-j^{-n} \over j-1} \right) \end{align}

Now, let $R=\sum_{j=2}^\infty \frac{1}{k^j} \left( {1-j^{-n} \over j-1} \right)$, then obviously $R>0$. But also: \begin{align} R &=\sum_{j=2}^\infty \frac{1}{k^j} \left( {1-j^{-n} \over j-1} \right) \\&\leq \sum_{j=2}^\infty \frac{1}{k^j} \left( {1 \over j-1} \right) \\&= \frac{1}{k} \sum_{j=1}^\infty {1 \over j k^j} = {-\log \left(1-\frac{1}{k} \right) \over k} \\&\leq {-\log \left(1-\frac{1}{2} \right) \over k} ={\log 2 \over k} \\&< \frac{1}{k} \end{align}

So that $0<R<\frac{1}{k}$.

Write $n=ak+b$, where $a,b \in \Bbb{Z}$, $a \geq 0$ and $0 \leq b \leq k-1$. Then we have:

$\displaystyle \quad \; {n \over k} = a+{b \over k} \\ \Rightarrow a \leq {n \over k} \leq a+{k-1 \over k} \\ \Rightarrow \left\lfloor {n \over k} \right\rfloor = a$.

And we also have:

$\displaystyle \quad \; a+R \leq {n \over k}+R \leq a+{k-1 \over k}+R \\ \Rightarrow a<a+R \leq {n \over k}+R \leq a+{k-1 \over k}+R<a+{k-1 \over k}+{1 \over k} \\ \Rightarrow a< {n \over k}+R<a+1 \\ \Rightarrow \left \lfloor {n \over k}+R \right \rfloor = a$

Finally, since $\sum_{s=1}^n \operatorname{Li}_s\left( \frac{1}{k} \right)={n \over k}+R$, we have $$\left \lfloor \sum_{s=1}^n \operatorname{Li}_s\left( \frac{1}{k} \right) \right \rfloor = a = \left \lfloor {n \over k} \right \rfloor$$

| cite | improve this answer | |
  • $\begingroup$ Oh hell. I wrote this answer thinking no body responded because I left the page unrefreshed from yesterday in my browser. If this is the same as some other proof that was posted, I apologize. $\endgroup$ – Fujoyaki Sep 29 '14 at 22:46
  • $\begingroup$ No problem, thank you for your proof. $\endgroup$ – user153012 Sep 29 '14 at 23:19

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.